The Influence of Digital Competence, Motivation, and Organizational Culture on Employee Performance in Electronic Retail - Arief Dermawan; Tri Gunarsih; Lucia Ika Fitriastuti; Yohannes Vemberi; Saifudin Zuhri (Lembaga Bale Literasi, 2026)
The rapid development of digital technology has encouraged electronic retail companies to improve the quality of human resources to be able to adapt to changes in the dynamic business environment. Digital competencies, motivation, and organizational culture are seen as important factors that can affect employee performance levels. This study aims to analyze the influence of digital competence, motivation, and organizational culture on employee performance in electronic retail companies in the Special Region of Yogyakarta (DIY). This study uses a quantitative approach with data sources in the form of primary data obtained through the distribution of questionnaires to employees of electronic retail companies in the DIY area. The number of respondents in this study was 100 people. The data analysis technique uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of the SmartPLS application. The results of the study show that digital competence affects employee performance. Motivation also affects employee performance. In addition, organizational culture has been proven to have an effect on employee performance. Therefore, improving employee performance in electronic retail companies in DIY can be done through strengthening digital competencies, increasing work motivation, and developing an organizational culture that supports innovation, collaboration, and adaptation to digital technology developments.